Chinese Consensus Statement on the Evaluation and Intervention of Collateral Circulation for Ischemic Stroke. (5th February 2014) - Liu, Li‐Ping; Xu, An‐Ding; Wong, Lawrence K.S.; Wang, David Z.; Wang, Yong‐Jun; ,
Summary Background Collateral circulation is becoming more significant in the individual management strategy of ischemic stroke, there are more data updated recently. Aim To make the further acknowledgment of the evaluation and how to improving collateral flow, for better treatment selection. Method A panel of experts on stroke providing related statement based on review the results from most up‐to‐date clinical research. Results DSA is the gold standard in evaluating all levels of collaterals. CTA can be used for evaluating leptomeningeal collaterals, MRA for CoW, TCD or TCCS can be used as screening tool for primary evaluation. The treatment modalities include direct interventions, such as Extracranial–Intracranial bypass, and indirect interventions, as External counterpulsation and pressor therapy. The consideration of methodology to augment and improve can be considered on an individual basis. Discussion In this consensus, we interpret the definition, neuroimaging evaluation, intervention and potential strategy on collaterals in the future. Conclusion Assessment of collateral circulation is crucial for selecting therapeutic options, predicting infarction volume and making prognosis after ischemic stroke. Data is still needed to provide therapeutic evidence for many new developed technologies. Until more evidence is available, the clinical significance of applying the new technologies is unclear and perhaps limited.